Development of oral dispersible tablets containing prednisolone nanoparticles for the management of pediatric asthma - Chen, Yi-Dan (Drug Des Devel Ther, 2015)
The purpose of the present study was to develop oral dispersible tablets containing prednisolone (PDS)-loaded chitosan nanoparticles using microcrystalline cellulose (MCC 101), lactose, and croscarmellose sodium (CCS). The PDS-loaded chitosan nanoparticles were formulated by ionotropic external gelation technique in order to enhance the solubility of PDS in salivary pH. Prepared nanoparticles were used for the development of oral fast disintegrating tablets by direct compression method. The prepared tablets were evaluated for disintegration time (DT), in vitro drug release (DR), thickness, weight variation, drug content uniformity, friability, and hardness. The effect of concentrations of the dependent variables (MCC, lactose, CCS) on DT and in vitro DR was studied. Fast disintegrating tablets of PDS can be prepared by using MCC, CCS, and lactose with enhanced solubility of PDS. The minimum DT was found to be 15 seconds, and the maximum DR within 30 minutes was 98.50%. All independent variables selected for the study were statistically significant. Oral fast disintegrating tablets containing PDS nanoparticles could be the better choice for the pediatric patients that would result in better patient compliance. From this study, it can be concluded that fast disintegrating tablets could be a potential drug delivery technology for the management of asthma in pediatrics.